Association of viral load with TRAIL, IP-10, CRP biomarker signature and disease severity in children with respiratory tract infection or fever without source: a prospective, multicentre cohort study - Papan, Cihan; Argentiero, Alberto; Adams, Ortwin; Porwoll, Marian; Hakim, Ummaya; Farinelli, Edoardo; Testa, Ilaria; Pasticci, Maria B.; Mezzetti, Daniele; Perruccio, Katia; Simon, Arne; Liese, Johannes G.; et al. (Journal of medical virology, 2023)
Background To investigate the association of viral load (VL) with (i) tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), interferon gamma-induced protein-10, C-reactive protein, and a combinatorial score (BV score), and (ii) clinical severity. Study Design In this prospective, multicentre cohort substudy, children with respiratory tract infection or fever without source were enrolled. VL for influenza virus, rhinovirus, respiratory syncytial virus, and adenovirus was measured from nasopharyngeal swabs. The reference standard diagnosis was established based on expert panel adjudication. Results Of 1140 recruited patients, 333 had a virus monodetection. VL for the aggregated data set correlated with TRAIL and IP-10 levels, with the length of oxygen therapy, and inversely with the BV score. At a single viral level, only the influenza VL yielded a correlation with TRAIL, IP-10 levels, and the BV score. Children with a viral reference standard diagnosis had significantly higher VL than those with bacterial infection (p = 0.0005). Low TRAIL (incidence rate ratio [IRR] 0.6, 95% confidence interval [CI] 0.39-0.91) and young age (IRR 0.62, 95% CI 0.49-0.79) were associated with a longer hospital stay, while young age (IRR 0.33, 95% CI 0.18-0.61), low TRAIL (IRR 0.25, 95% CI 0.08-0.76), and high VL (IRR 1.16, 95% CI 1.00-1.33) were predictive of longer oxygen therapy. Conclusion These findings indicate that VL correlates with biomarkers and may serve as a complementary tool pertaining to disease severity.
First published: 31 August 2022
Gesehen am 25.05.2023